Where Community Happens The Kibbutz and the Philosophy of Communalism - Near, Henry (Ralahine Utopian Studies, 2011)
In reaction to the spread of globalization, recent years have seen considerable growth in the number of intentional communities established across the world. In this collection of articles and lectures, many of them previously unpublished in English, the author analyzes various aspects of the philosophy of the kibbutz and draws parallels with other societies and philosophical trends, in the hope that a close look at the ways of thought of the kibbutz - arguably the best-established communalist society - may help other communalists crystallize their own social philosophies. Utopian thought and communal experience are brought to life through the extensive use of the voices of some of the most influential thinkers and kibbutz members of the past hundred years, including Martin Buber and David Ben Gurion.